1995
DOI: 10.1210/jc.80.12.3585
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults with growth hormone (GH) deficiency: response to treatment with recombinant human GH in a placebo-controlled 21-month trial

Abstract: We examined the effect of GH supplementation on the psychological capacity and sense of well-being in 36 patients with adult-onset GH deficiency (GHD). Recombinant human GH was given in a 21-month cross-over, double blind trial, and quality of life was assessed by using three self-rating questionnaires: the Hopkins Symptom Check List (HSCL), the Nottingham Health Profile (NHP), and the Psychological General Well-Being index. In addition, at the final examination the spouses completed a short questionnaire conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 0 publications
2
52
2
2
Order By: Relevance
“…Burman et al (5) have documented the effects of GHD and GHRT on quality of life and on cognition by the use of self-rating tests (psychological parameters, including cognition, have been assessed by a subscale of the Hopkins Symptom Check List) and by a partner questionnaire which are not formal tests on cognition. When compared with healthy controls, more problems in cognitive function in patients with AO GHD (15 females and 21 males) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Burman et al (5) have documented the effects of GHD and GHRT on quality of life and on cognition by the use of self-rating tests (psychological parameters, including cognition, have been assessed by a subscale of the Hopkins Symptom Check List) and by a partner questionnaire which are not formal tests on cognition. When compared with healthy controls, more problems in cognitive function in patients with AO GHD (15 females and 21 males) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years much interest has been expressed, and effort expanded, about the possibility that cognitive function is related to insulin-like growth factor-I (IGF-I) and GH. Indeed, impaired cognitive function has been demonstrated in adults with childhood-onset GHD (CO GHD) (2) and in adult-onset GHD (AO GHD) (5). In addition, a few studies have demonstrated that GH replacement therapy (GHRT), in both adults with CO GHD and AO GHD, has beneficial effects on cognitive deficits (3,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest clinical trials that reported improvement in QoL in patients who received GH were conducted by Mårdh et al (22) and Wallymahmed et al (nZ32) (7). In almost all of these studies, the benefits of GH were revealed by some, but not all instruments employed and/or were attributed to certain, but not all, dimensions measured; finally, they seemed to be heavily dependent on the degree of the initial impairment and were partly related to placebo effect.…”
Section: Introductionmentioning
confidence: 99%
“…Quando comparados com pacientes recebendo placebo, pacientes adultos usando GH relatam melhora no humor, na energia, no bem estar, na qualidade do sono e na qualidade de vida em geral (33). Existe melhora também na tolerância ao exercício, por incremento da massa e força muscular e por melhora da capacidade cardíaca em decorrência do aumento da fração de ejeção do ventrículo esquerdo, do débito cardíaco e da redução da resistência vascular periférica (27).…”
Section: Benefícios Da Reposição De Gh Em Adultosunclassified